Method for producing regenerated water absorptive resin composition

JP2025025614APending Publication Date: 2025-02-21NIPPON SHOKUBAI CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023130513
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0022】 本発明によって、過度の精製や過剰な精製剤も必要とせずに、異物(パルプなど)が乾燥と同時に除去できた。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025025614000001_ABST
    Figure 2025025614000001_ABST
Patent Text Reader

Abstract

To provide a method for obtaining a regenerated water absorptive resin in which a foreign matter from a used water absorptive resin, coloration, reduction in a residual monomer and deterioration are suppressed without excessive consumption of resources by recycling.SOLUTION: A method for producing a regenerated water absorptive resin containing a used water absorptive resin or its solubilized matter as a part of a raw material flows water-containing gel particles which have been heated at 40°C or higher in a container rotation type drier or a flow drier, and heats and dries the water-containing gel particles under a gas flow, in a step (A) of drying a water-containing gel of a used water absorptive resin after purification or a step (B) of drying a water-containing gel of a water absorptive resin obtained using a used water absorptive resin after purification or its solubilized matter as a part of a raw material, in a method for producing a water absorptive resin including a step of polymerizing an unsaturated monomer aqueous solution.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a recycled water-absorbent resin composition using a used water-absorbent resin or a solubilized product thereof (a decomposition product of a water-absorbent resin) as a raw material. [Background technology]

[0002] In recent years, water-absorbent resins have been widely used as constituent materials for absorbent articles such as paper diapers, sanitary napkins, incontinence pads, absorbent sheets, cat litter, etc., from the viewpoint of absorbing body fluids. Although absorbent articles, which are the main application of water-absorbent resins, are generally disposable, there has been growing interest in recycling sanitary products such as paper diapers due to the increasing environmental awareness.

[0003] One proposed method for recycling used sanitary products (for example, disposable diapers that have absorbed human waste) involves collecting the used sanitary products, separating them into their component parts such as pulp, nonwoven fabric, adhesive, and water-absorbent resin, and then washing, refining, sterilizing, and bleaching them before recycling.

[0004] Among these components, water-absorbent resins swell by absorbing the cleaning water and sterilizing water in the recycling process, and the urine contained in the cleaning water in the cleaning process, so they need to be washed and dried before they can be reused as products, and it is known that they deteriorate and become discolored due to the heat during drying. For this reason, recycling water-absorbent resins has been technically difficult.

[0005] Conventionally, technology has been proposed to solubilize used water-absorbent resin with a decomposing agent in order to recover pulp, nonwoven fabric, adhesives, etc. from sanitary products. However, since water-absorbent resin is difficult to recycle or separate, it has generally been solubilized to separate the pulp, etc., and then disposed of.

[0006] However, in recent years, a technology has been developed for separating and regenerating used water-absorbent resins for use in absorbent articles, and recycling them into water-absorbent resins or other useful substances (e.g., water-soluble polymers and adhesives).

[0007] As a method for recycling used water-absorbent resin, a method has been proposed in which the used water-absorbent resin is separated from used absorbent articles (particularly sanitary products such as paper diapers), purified, and reused (Patent Documents 1 to 3).

[0008] A recycled water absorbent resin composition obtained from a used water absorbent resin is reused as a water absorbent resin as it is. However, since a performance of a recycled water absorbent resin composition is generally deteriorated in a recycling process, the use of the recycled water absorbent resin composition is actually limited.

[0009] In view of this, as applications of the recycled water absorbent resin composition, which is likely to be accompanied by a decrease in performance due to recycling, methods have been proposed for reducing the amount of raw materials used for the water absorbent resin and restoring the performance of the recycled water absorbent resin composition by using the recycled water absorbent resin composition as a raw material for the water absorbent resin (Patent Document 6) or using a solubilized matter of used water absorbent resin as a raw material for the water absorbent resin (Patent Documents 4, 7 to 11).

[0010] However, in the case of a used water absorbent resin (particularly a water absorbent resin separated from a used sanitary product), since the water absorbent resin absorbs water and swells, it is difficult to control the separation of water-soluble components such as urine, and further, when separating the water absorbent resin, there has been a problem that foreign matter such as pulp or nonwoven fabric is mixed into the separated water absorbent resin due to the stickiness of the water absorbent resin after swelling.

[0011] Foreign matter such as a urine component or pulp remaining in a recycled water absorbent resin composition obtained from a used water absorbent resin is likely to cause discoloration of the water absorbent resin, an increase in residual monomers, and a decrease in water absorption performance through a production process for the water absorbent resin involving heating.

[0012] That is, although the water-absorbent resin is white, since its main application is paper diapers, a recycled water-absorbent resin composition made from used water-absorbent resin as a raw material has problems of coloring and odor derived from feces and urine, and in order to solve such problems (coloring and odor), bleaching and sterilization have been required in the process of recycling used water-absorbent resin.

[0013] In addition, a method for removing foreign matter such as pulp from a recycled water-absorbent resin composition has been proposed (Patent Document 6), and a technique for adding silica or unused water-absorbent resin in a drying process has also been proposed in order to improve the coloring of a recycled water-absorbent resin composition (Patent Documents 8 and 9).

[0014] However, in the conventional regeneration method, in order to remove impurities (particularly urine components and pulp foreign matter) in the used water absorbent resin, not only does the quality of the regenerated water absorbent resin composition decrease and productivity decrease, but also the regenerated water absorbent resin composition is required to be out of spec or to be subjected to excessive post-treatment (regeneration treatment), and excessive bleaching, sterilization, washing, removal of foreign matter, and use of other additives in recycling the water absorbent resin not only increase the regeneration cost and deteriorate the regenerated water absorbent resin composition, but are also undesirable from the viewpoint of the consumed resources and energy, and from the balance between the regenerated resources and the consumed resources involved in regeneration. In addition, impurities remaining in the used water absorbent resin and chemicals (bactericides, decomposers, etc.) used in the refining process thereof inhibit the polymerization of the water absorbent resin, and are likely to cause an increase in the residual monomers of the water absorbent resin and a decrease in its performance.

[0015] Many recycling methods for used water absorbent resins have been proposed, including those in Patent Documents 1 to 11, but the regeneration process of used water absorbent resins has problems of contamination with foreign matter such as pulp and coloring. There are significant restrictions on using a regenerated water absorbent resin composition as a water absorbent resin, or using used water absorbent resins or their solubilized products as raw materials for water absorbent resins. [Prior art documents] [Patent documents]

[0016] [Patent Document 1] International Publication No. WO2019 / 087485 [Patent Document 2] International Publication No. WO2019 / 151538 [Patent Document 3] International Publication No. WO2021 / 075506 [Patent Document 4] International Publication No. WO2020 / 241025 [Patent Document 5] International Publication No. WO2021 / 205780 [Patent Document 6] International Publication No. WO2021 / 044690 [Patent Document 7] International Publication No. WO2020 / 213298 [Patent Document 8] International Publication No. WO2022 / 080342 [Patent Document 9] International Publication No. WO2022 / 081523 [Patent Document 10] International Publication No. WO2022 / 082163 [Patent Document 11] International Publication No. WO2022 / 082165 Summary of the Invention [Problem to be solved by the invention]

[0017] To provide a method for obtaining a recycled water-absorbent resin composition having little foreign matter, coloration or residual monomers from a used water-absorbent resin without excessive consumption of resources in recycling.

[0018] While various methods for producing a recycled water absorbent resin composition, particularly methods for purifying a used water absorbent resin, have been proposed, such as Patent Documents 1 to 11, the present inventors have solved the above problems (coloration, foreign matter, performance) by not sticking to improvements in purification of conventional recycled water absorbent resin compositions, nor by excessive purification, but by selecting a specific drying method for solving the problems in the drying step of the recycled water absorbent resin composition, which has not been focused on in the present solution, and more preferably by selecting a specific additive in the specific step of the recycled water absorbent resin composition.

[0019] That is, while many regeneration methods for used water absorbent resins, regeneration reagents, and solubilization methods for water absorbent resins for recycling have been proposed, the present invention has focused for the first time on a drying step, which has hardly been paid attention to in conventional recycling methods for water absorbent resins, in conventional regeneration methods and regeneration using used water absorbent resins as raw materials, and solved the problem. [Means for solving the problem]

[0020] The present inventors have conducted intensive research to solve the above problems. As a result, they have found that, in producing a recycled water absorbent resin composition using a used water absorbent resin or a solubilized product thereof as a part or all of a raw material, one of the causes of coloring is urea present in urine and ammonia, which is a decomposition product thereof, and further found that the above problems can be solved by performing a specific drying, which has led to the completion of the present invention.

[0021] That is, the present invention provides a method for producing a recycled water-absorbent resin composition using a used water-absorbent resin or a solubilized product thereof as a part or all of a raw material, the method comprising (A) a drying step of a hydrogel-like crosslinked polymer derived from a purified used water-absorbent resin, or (B) a polymerization step of an unsaturated monomer aqueous solution, in which in a drying step of a hydrogel-like crosslinked polymer obtained by using a purified used water-absorbent resin or a solubilized product thereof as a part of a raw material, the hydrogel-like crosslinked polymer previously heated to 40°C or higher is fluidized in a container rotary dryer or a fluidized dryer and heated and dried under an air flow. Effect of the Invention

[0022] The present invention allows foreign matter (such as pulp) to be removed simultaneously with drying without the need for excessive refining or excessive use of refining agents. [Brief description of the drawings]

[0023] [Figure 1] 1 is a schematic diagram showing a drying device (a rotary container dryer with a lifting blade) according to one embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic diagram showing a drying device (a container rotary dryer with a heating tube) according to one embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic diagram showing a drying device (fluidized bed dryer) according to one embodiment of the present invention. [Figure 4] FIG. 1 is a schematic diagram showing an agitation dryer (paddle dryer). [Diagram 5]FIG. 1 is a schematic diagram showing a ventilation band type dryer. [Figure 6] FIG. 1 is a schematic diagram showing a drum dryer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] The present invention relates to a method for producing a recycled water-absorbent resin composition using a used water-absorbent resin or a solubilized product thereof as a part or all of a raw material, and the method for producing a recycled water-absorbent resin composition includes (A) a drying step of a hydrous gel-like crosslinked polymer derived from a purified used water-absorbent resin, or (B) a polymerization step of an unsaturated monomer aqueous solution, and in the drying step of a hydrous gel-like crosslinked polymer obtained by using a purified used water-absorbent resin or a solubilized product thereof as a part of a raw material, the hydrous gel-like crosslinked polymer previously heated to 40°C or higher is fluidized in a container rotary dryer or a fluidized dryer and heated and dried under an air flow.

[0025] Each of the configurations will be described below.

[0026] (1) A hydrous gel-like cross-linked polymer to be dried In the method for producing a recycled water absorbent resin composition of the present invention, the hydrogel crosslinked polymer to be dried (hereinafter, abbreviated as "hydrogel") is (A) Hydrogel derived from used water absorbent resin after purification; (B) A hydrogel obtained by using a purified used water absorbent resin or a solubilized product thereof as a part of a raw material in a production process of a recycled water absorbent resin composition including a polymerization process of an unsaturated monomer aqueous solution; Examples include:

[0027] Here, in the above (A), only the hydrous gel of the used water absorbent resin is dried for the purpose of regenerating the used water absorbent resin. In other words, (A) corresponds to a method for producing a regenerated water absorbent resin composition using the used water absorbent resin or its solubilized product as the entire raw material. On the other hand, the above (B) corresponds to a method for producing a regenerated water absorbent resin composition using the used water absorbent resin or its solubilized product as part of the raw material. In other words, in (B), a mixture of the used water absorbent resin or its solubilized product and unused water absorbent resin is dried.

[0028] In addition, a water absorbent resin obtained by using a used water absorbent resin or a solubilized product thereof as a part or all of a raw material is called a "recycled water absorbent resin composition". The recycled water absorbent resin composition may be a water absorbent resin before surface cross-linking or a water absorbent resin after surface cross-linking, regardless of whether or not the surface cross-linking is performed, but a water absorbent resin after surface cross-linking is preferable. The water absorbent resin before surface cross-linking may also be called a water absorbent resin precursor.

[0029] (Used water-absorbent resin) In the present invention, the term "used water absorbent resin" refers to a water absorbent resin contained in an absorbent article processed by a user of the water absorbent resin after shipment from a water absorbent resin factory; an absorbent article in which the absorbent article is sold and distributed and used by a consumer; or an absorbent article discarded after use. In addition, the used water absorbent resin may include a discarded water absorbent resin generated in the manufacturing process of the water absorbent resin, or a water absorbent resin contained in a water absorbent article discarded before use.

[0030] (Solubilized material of used water absorbent resin) In the present invention, the term "solubilized product of used water absorbent resin" means a polymer obtained by solubilizing the above-mentioned used water absorbent resin. More specifically, it means a polymer obtained by solubilizing the water absorbent resin by decomposing the main chain or crosslinking points of the water absorbent resin. The degree of solubilization and the molecular weight are appropriately determined, but the solubilization rate (mass%) of the water absorbent resin after the decomposition treatment is preferably high, and the water-soluble content (measured by pH titration after 16 hours extraction per 1.0 g of water absorbent resin) specified in EDANA470.02-02 (2002) is preferably 30 mass% or more, 50 mass% or more, 60 mass% or more, 70 mass% or more, 80 mass% or more, 90 mass% or more, and particularly 100 mass%. If the solubilization rate is low, the applications are limited both as a water absorbent resin and as a water-soluble resin, and this is not preferable. In particular, when the resin is used as a raw material for a water absorbent resin, the performance (for example, water absorption ratio) of the obtained water absorbent resin may be reduced. The mass average molecular weight Mw of the solubilized product is from 100 to 5,000,000, and the number average molecular weight is from 10,000 to 1,000,000, or from 100,000 to 800,000.

[0031] In the present invention, as a method for solubilizing a used water absorbent resin, the decomposition methods disclosed in the above Patent Documents 4 to 8 and other known documents are appropriately applied. Other known documents include, for example, JP-A-6-313008 (persulfate), JP-A-4-317784 (heat treatment at 40 ° C. in the presence of an oxidizing agent), JP-A-5-247307 (ascorbic acid), JP-A-2001-316519 (periodate), JP-A-9-249711 (acid or alkali), and JP-A-2020-116569 (water-soluble reducing agent and iron ions and / or copper ions). As long as a solubilized product of a used water absorbent resin can be obtained, there is no particular restriction.

[0032] (Method for producing a recycled water-absorbent resin composition using used water-absorbent resin or its solubilized material as a part or all of the raw material) In the present invention, the method for producing a recycled water absorbent resin composition using a used water absorbent resin or a solubilized product thereof as a part or all of a raw material is not particularly limited, and examples thereof include the following production methods (1) to (4).

[0033] In other words, (1) A method for producing a recycled water-absorbent resin composition, as described in the above Patent Documents 1 to 3, which comprises separating and purifying a used water-absorbent resin from a used absorbent article (e.g., a used sanitary product) to obtain a hydrogel, and drying the resulting hydrogel; (2) As in the above Patent Documents 4, 7 to 11, a method for producing a recycled water absorbent resin composition, in which a used water absorbent resin is separated from a used absorbent article (e.g., a used sanitary product), and the solubilized water absorbent resin is applied to a production process of the water absorbent resin (e.g., a polymerization process); (3) As described in Patent Document 6, a method for producing a mixture of a recycled water absorbent resin composition and a virgin water absorbent resin by separating and purifying a used water absorbent resin from a used absorbent article (e.g., a used sanitary product), drying the purified water absorbent resin, and applying the resulting recycled water absorbent resin composition to a production process for a water absorbent resin (e.g., a surface cross-linking process); (4) A method for producing a recycled water-absorbent resin composition by separating a used water-absorbent resin from a used absorbent article (e.g., a used sanitary product), solubilizing the solubilized water-absorbent resin, and re-crosslinking the solubilized water-absorbent resin (e.g., JP 2020-049398 A); Either of the above applies.

[0034] Here, the above (1) includes the drying of the above (A). The above (2) includes the drying of the above (B). In addition, the above (3) and (4) use the solubilized product of the used water absorbent resin after purification as part of the raw materials (however, in (4), most of the raw materials are other than the crosslinking agent) in the manufacturing process of the water absorbent resin, and the manufacturing process includes drying. In other words, all of the manufacturing methods (1) to (4) above have a drying process of the hydrogel of the used water absorbent resin or its solubilized product.

[0035] In the present invention, it is only necessary to include a step of drying a hydrogel of a used water absorbent resin or a solubilized product thereof, and other steps for producing a water absorbent resin, such as a polymerization step and a surface cross-linking step, may be known methods or methods that are currently novel, and are not particularly limited.

[0036] (Hydrate gel derived from used water-absorbent resin) The present invention assumes the recycling of water-absorbent resin from used absorbent articles (for example, used paper diapers with feces and urine attached thereto). Since such water-absorbent resin absorbs feces and urine and swells, when recycling, it is necessary to perform washing treatment, dehydration treatment, and sterilization treatment as necessary for the collected water-absorbent resin. Through the treatment, it becomes a hydrous gel derived from the used water-absorbent resin after purification. For the above-mentioned washing treatment, dehydration treatment, and sterilization treatment, the methods disclosed in the above-mentioned Patent Documents 1 to 3 and other known documents, for example, WO2021 / 162082, WO2022 / 091975, WO2023 / 007871, WO92 / 007995, JP-A-2013-150977, JP-A-2003-326161, etc. can be appropriately selected. In addition, there is no particular restriction as long as a hydrous gel of the used water-absorbent resin after purification can be obtained. The hydrogel of the used water-absorbent resin of the present invention preferably has a solid content of 1% by mass or more and 95% by mass or less, and more preferably 10% by mass or more and 90% by mass or less.

[0037] In the present invention, when a used water absorbent resin or a solubilized product thereof is used as a part of a raw material, the used water absorbent resin or a solubilized product thereof is mixed with a water absorbent resin in the middle of production (particularly, an aqueous monomer solution before polymerization or a hydrous gel during or after polymerization) in a production process of a recycled water absorbent resin composition, preferably in a process before a drying process, particularly preferably in an arbitrary process between the polymerization process and the drying process.

[0038] The mixing ratio of the used water absorbent resin or a solubilized product thereof to the water absorbent resin in the middle of production is preferably 1 mass % or more and 60 mass % or less, more preferably 3 mass % or more and 50 mass % or less, particularly preferably 5 mass % or more and 40 mass % or less, based on the solid content of the monomer or hydrous gel of the water absorbent resin in the middle of production.

[0039] (Physical properties of hydrous gel) In the present invention, the hydrogel obtained by using a used water absorbent resin or a solubilized product thereof as a part or all of a raw material has a solid content of preferably 10 mass % or more and 90 mass % or less, more preferably 20 mass % or more and 80 mass % or less, further preferably 30 mass % or more and 70 mass % or less, particularly preferably 40 mass % or more and 60 mass % or less, in order to solve the problems of the present invention.

[0040] The residual monomer content of the hydrogel is preferably as small as possible, preferably 2% by mass or less, more preferably 1% by mass or less, and even more preferably 0.5% by mass or less. If the residual monomer content is large, drying may become difficult, and coloring after drying or acrylamide, which is an impurity specific to recycling, may be produced as a by-product.

[0041] The CRC of the above-mentioned hydrogel is, in terms of dry mass, preferably 5 g / g or more and 80 g / g or less, more preferably 10 g / g or more and 50 g / g or less, even more preferably 15 g / g or more and 45 g / g or less, and particularly preferably 20 g / g or more and 40 g / g or less.

[0042] The water-soluble content (Ext) of the above-mentioned hydrogel is preferably 20% by mass or less, more preferably 15% by mass or less, further preferably 10% by mass or less, and particularly preferably 5% by mass or less, calculated on a dry mass basis.

[0043] (Temperature of hydrous gel) In the present invention, the hydrogel obtained by using the used water absorbent resin or its solubilized product as a part or all of the raw material is preferably heated to 40°C or higher, more preferably 50°C or higher, and even more preferably 60°C or higher in order to solve the problems of the present invention. On the other hand, in terms of effect and energy, it is preferably 110°C or lower, more preferably 100°C or lower, and even more preferably 90°C or lower. The temperature of the hydrogel can be appropriately adjusted in consideration of the polymerization temperature, aging after polymerization, heating or cooling, etc. Note that if the temperature of the hydrogel before drying is excessively high, it is not preferable because it may cause coloring of the obtained recycled water absorbent resin composition.

[0044] (Shape of hydrogel) In the present invention, the hydrogel obtained by using a used water-absorbing resin or a solubilized product thereof as a part or all of the raw material is preferably in the form of particles. The mass-average particle size of the hydrogel is preferably 3 mm or less, more preferably 2 mm or less, 1 mm or less, 800 μm or less, 500 μm or less, and most preferably 400 μm or less. From the viewpoint of effectiveness, the lower limit is about 100 μm. By keeping the size within this range, it becomes easy to remove foreign matter (particularly pulp and fine particles) by air flow during drying.

[0045] In addition, the recycled water-absorbent resin composition is prone to a decrease in water absorption rate compared to unused water-absorbent resin due to impurities and damage during the regeneration process, but the water absorption rate can be restored or improved by setting the particle size of the hydrous gel before drying to the above range, particularly by crushing the gel to the above range.

[0046] The hydrogel before drying can also be obtained by classification or selection, and the particle size of the hydrogel can also be controlled by polymerization. From the viewpoint of ease of particle size control, however, it is preferable to include a gel crushing step before drying and to achieve a particle size in the above-mentioned range by the gel crushing.

[0047] (2) Gel fluidizing agent In the manufacturing method according to the present invention, the hydrogel in the drying step contains a surfactant or a crosslinking agent that reacts with a carboxyl group. In the gel crushing step, a gel fluidizing agent is added to the hydrogel, which makes it easier to agitate and dry the gel in particulate form, and makes it easier to remove foreign matter by airflow during drying or by classification after drying (particularly pulp and fine particles).

[0048] The amount of the gel fluidizer to be added is appropriately set depending on the water content of the hydrogel or particulate hydrogel and the type of the gel fluidizer, and is preferably 0.001% by mass or more and 0.5% by mass or less, more preferably 0.01% by mass or more and 0.3% by mass or less, and even more preferably 0.02% by mass or more and 0.2% by mass or less, based on the solid content of the hydrogel.

[0049] (Surfactant) The surfactants used in the present invention include anionic, cationic, nonionic and amphoteric surfactants, as well as low molecular weight or high molecular weight surfactants thereof, etc. Specifically, the surfactants are as follows, and two or more of them may be used in combination.

[0050] (a) a nonionic surfactant; Sucrose fatty acid esters, polyglycerol fatty acid esters, sorbitan fatty acid esters, polyoxyethylene sorbitan fatty acid esters, polyoxyethylene glycerol fatty acid esters, sorbitol fatty acid esters, polyoxyethylene sorbitol fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, alkylaryl formaldehyde condensed polyoxyethylene ethers, polyoxyethylene polyoxypropylene block copolymers, polyoxyethylene polyoxypropyl alkyl ethers, polyethylene glycol fatty acid esters, alkyl glucosides, N-alkyl gluconamides, polyoxyethylene fatty acid amides, polyoxyethylene alkylamines, phosphate esters of polyoxyethylene alkyl ethers, and phosphate esters of polyoxyethylene alkyl allyl ethers.

[0051] (b) amphoteric surfactants; Alkyl dimethylaminoacetic acid betaines such as capryl dimethylaminoacetic acid betaine, lauryl dimethylaminoacetic acid betaine, myristyl dimethylaminoacetic acid betaine, and stearyl dimethylaminoacetic acid betaine; alkyl amidopropyl betaines such as lauric acid amidopropyl betaine, coconut oil fatty acid amidopropyl betaine, and palm kernel oil fatty acid amidopropyl betaine; alkyl hydroxysulfobetaines such as lauryl hydroxysulfobetaine; and alkyl carboxymethyl hydroxyethyl imidazolinium betaines such as 2-alkyl-N-carboxymethyl-N-hydroxyethyl imidazolinium betaine.

[0052] (c) anionic surfactants; Monoalkali metal alkylaminodiacetates such as monosodium laurylaminodiacetate, potassium laurylaminodiacetate, and sodium myristylaminodiacetate;

[0053] (d) cationic surfactants; Long-chain alkyl dimethylaminoethyl quaternary salts, etc.

[0054] (polymer lubricant) In the production method according to the present invention, the following polymer lubricants may be added to the aqueous monomer solution or hydrous gel as long as the object of the present invention is achieved.

[0055] Specific examples of the polymer lubricant include maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, maleic anhydride-modified ethylene-propylene copolymer, maleic anhydride-modified ethylene-propylene-diene terpolymer (EPDM), maleic anhydride-modified polybutadiene, maleic anhydride-ethylene copolymer, maleic anhydride-propylene copolymer, maleic anhydride-ethylene-propylene copolymer, maleic anhydride-butadiene copolymer, polyethylene, polypropylene, ethylene-propylene copolymer, oxidized polyethylene, oxidized polypropylene, oxidized ethylene-propylene copolymer, ethylene-acrylic acid copolymer, polyalkylene oxide such as ethyl cellulose, ethylhydroxyethyl cellulose, and polyethylene glycol. Two or more of these may be used in combination.

[0056] The molecular weight (mass average molecular weight) of the polymer lubricant is preferably 200 or more and 2 million or less, and more preferably 400 or more and 1 million or less.

[0057] Furthermore, as the gel fluidizing agent, these polymeric lubricants may be used in combination with the above-mentioned surfactants.

[0058] When a surfactant and a polymer lubricant are used in combination, the total amount added is appropriately set according to the polymerization form, the composition of the aqueous monomer solution, and the water content of the hydrogel. When added to the aqueous monomer solution, the total amount is set relative to the monomer component, when added to the aqueous monomer solution, the total amount is set relative to the solid content of the hydrogel, and when added to both, the total amount is set relative to the solid content of the hydrogel. Specifically, the total amount is preferably 1.0% by mass or less, more preferably 0.5% by mass or less, and preferably 0.05% by mass or more, more preferably 0.1% by mass or more, relative to the solid content of the hydrogel to be dried.

[0059] (surface tension) In the present invention, the gel fluidizer may be selected in consideration of the fluidity of the hydrogel to be dried. In addition, the type and amount of the gel fluidizer that do not excessively reduce the surface tension of the final product are preferred, taking into consideration the amount of resorption during actual use of the absorbent article (paper diaper) using the obtained recycled water absorbent resin composition. For example, the type and amount of the gel fluidizer are selected so that the surface tension of the final product (surface tension of the dispersion of the water absorbent resin in physiological saline) is preferably 55 mN / m or more, more preferably 60 mN / m or more, and even more preferably 65 mN / m or more.

[0060] (Residual urea amount) In the present invention, by subjecting a used water absorbent resin to a urea removal treatment such as washing, it is possible to reduce impurities derived from human waste contained in the water absorbent resin, thereby reducing coloration of the recycled water absorbent resin composition.

[0061] Among impurities derived from human waste, urea is known to have a high content and / or amount, and by setting the content of the urea to 4% by mass or less, 3% by mass or less, 2% by mass or less, 1.8% by mass or less, or 1.6% by mass or less, the deterioration of the water absorption performance of the recycled water absorbent resin composition can be prevented and coloring can be reduced. The lower the lower limit, the more preferable it is. However, in the present invention, even if some urea remains (for example, 0.01% by mass or even 0.1% by mass) without excessive purification, a recycled water absorbent resin composition with less coloring and less residual monomer can be obtained. In addition, excessive purification not only increases the cost of regeneration and deteriorates the recycled water absorbent resin composition, but is not preferable from the viewpoint of the consumed resources and energy, and the balance between the recycled resources and the consumed resources involved in regeneration. However, the present invention has an advantage in that such excessive purification is not required. The "amount of residual urea" means the urea content in the recycled water absorbent resin composition.

[0062] The method for quantifying the "amount of residual urea" is not particularly limited as long as it can quantify urea. For example, a method in which a water-absorbent resin is dispersed in water to extract the urea contained in the water-absorbent resin into an aqueous phase, and then the urea contained in the aqueous phase is directly quantified by liquid chromatography, gas chromatography, or the like. In addition, a method in which urea is quantified by a colorimetric method such as the urease-indophenol method or the diacetyl monoxime method may be used.

[0063] Furthermore, by washing or dehydrating the used water absorbent resin, the amount of urea contained in the used water absorbent resin can be reduced to a target range.

[0064] (3) A method for producing a hydrogel that is applied to a process for producing a recycled water-absorbent resin composition, which includes a polymerization step of an aqueous solution of an unsaturated monomer (B) The polymerization method for the hydrogel obtained by using the above-mentioned (B) used water-absorbent resin or its solubilized product as a part of the raw material will be described below.

[0065] (monomer) In the present invention, the monomer may be any monomer used in water absorbent resins, but typically an aqueous solution containing acrylic acid as a main component (hereinafter referred to as "monomer aqueous solution") is used. Note that a monomer slurry may also be used within a range in which the water absorption performance of the resulting recycled water absorbent resin composition is not reduced. For convenience, the monomer aqueous solution will be described in this section.

[0066] It means that the amount (content) of acrylic acid (salt) used is usually 50 mol % or more, preferably 70 mol % or more, and more preferably 90 mol % or more (upper limit: 100 mol %) based on the whole monomers (excluding the internal crosslinking agent) subjected to the polymerization reaction of the water absorbent resin.

[0067] The monomer other than acrylic acid may be any compound that can be polymerized to become a water-absorbent resin. Examples of the unsaturated monomers include methacrylic acid, (anhydrous) maleic acid, itaconic acid, cinnamic acid, vinyl sulfonic acid, allyl toluene sulfonic acid, vinyl toluene sulfonic acid, styrene sulfonic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, 2-(meth)acryloylethanesulfonic acid, 2-(meth)acryloylpropanesulfonic acid, and 2-hydroxyethyl (meth)acryloyl phosphate; amide group-containing unsaturated monomers such as (meth)acrylamide, N-ethyl (meth)acrylamide, and N,N-dimethyl (meth)acrylamide; amino group-containing unsaturated monomers such as N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylamide; mercapto group-containing unsaturated monomers; phenolic hydroxyl group-containing unsaturated monomers; and lactam group-containing unsaturated monomers such as N-vinylpyrrolidone.

[0068] Among these, the monomer other than acrylic acid is, from the viewpoint of the water absorption performance of the obtained water absorbent resin, an acid group-containing unsaturated monomer, more preferably methacrylic acid, maleic acid (anhydride), itaconic acid, cinnamic acid, and further preferably methacrylic acid.

[0069] In the case where an acid group-containing unsaturated monomer having an acid group such as a carboxyl group is used among acrylic acid and the above-mentioned monomers, it is more preferably an alkali metal salt, even more preferably at least one selected from the group consisting of sodium salts, lithium salts and potassium salts, and particularly preferably a sodium salt.

[0070] From the viewpoint of water absorption performance, the number of moles of the neutralization salt relative to the total number of moles of the acid group-containing unsaturated monomer and its neutralization salt (hereinafter referred to as "neutralization rate") is preferably 40 mol% or more, more preferably 40 mol% to 80 mol%, even more preferably 45 mol% to 78 mol%, and particularly preferably 50 mol% to 75 mol%. The adjustment of the neutralization rate may be performed before the start of the polymerization reaction of the acid group-containing unsaturated monomer, during the polymerization reaction of the acid group-containing unsaturated monomer, or on the hydrogel-like crosslinked polymer obtained after the polymerization reaction of the acid group-containing unsaturated monomer is completed. In addition, the neutralization rate may be adjusted by selecting one of the stages before the start of the polymerization reaction, during the polymerization reaction, or after the polymerization reaction is completed, or the neutralization rate may be adjusted at multiple stages.

[0071] (Internal crosslinking agent) In the present invention, an internal crosslinking agent is preferably used, which adjusts the water absorption performance and gel strength of the resulting recycled water-absorbent resin composition when it absorbs water.

[0072] The internal crosslinking agent may have a total of two or more unsaturated bonds or reactive functional groups in one molecule. For example, N,N-methylenebis(meth)acrylamide, (poly)ethylene glycol di(meth)acrylate, ethylene glycol diglycidyl ether, glycidyl (meth)acrylate, etc. may be mentioned. Among these, two or more may be used in combination. The amount of the internal crosslinking agent used is preferably 0.001 mol% or more and 5 mol% or less, more preferably 0.005 mol% or more and 2 mol% or less, based on the monomer.

[0073] (Amount of used water absorbent resin or its solubilized material added) In the above method (B), the used water absorbent resin or the solubilized product thereof is added to and mixed with the monomer or the hydrogel in the middle of production. The amount of the used water absorbent resin or the solubilized product thereof is preferably 1% by mass or more and 60% by mass or less, more preferably 3% by mass or more and 50% by mass or less, and further preferably 5% by mass or more and 40% by mass or less, based on the solid content of the monomer or the hydrogel in the middle of production.

[0074] (monomer concentration) In the present invention, the monomer concentration in the monomer composition (=total monomer amount / (total monomer amount+total polymerization solvent amount (usually water)) is preferably 10 mass% or more and 90 mass% or less, more preferably 20 mass% or more and 80 mass% or less, further preferably 30 mass% or more and 70 mass% or less, and particularly preferably 40 mass% or more and 60 mass% or less, from the viewpoint of the physical properties and productivity of the recycled water absorbent resin composition.

[0075] (Other additives) In the production method according to the present invention, the following substances (hereinafter referred to as "other substances") may be added to the aqueous monomer solution within the scope of achieving the object of the present invention.

[0076] Specific examples of other substances include chain transfer agents such as thiols, thiolic acids, secondary alcohols, amines, and hypophosphites; foaming agents such as carbonates, bicarbonates, azo compounds, and bubbles; chelating agents such as ethylenediaminetetra(methylenephosphinic acid) and metal salts thereof, ethylenediaminetetraacetic acid and metal salts thereof, and diethylenetriaminepentaacetic acid and metal salts thereof; hydrophilic polymers such as polyacrylic acid (salts) and crosslinked products thereof (for example, recycled water-absorbent resin fine powder), starch, cellulose, starch-cellulose derivatives, and polyvinyl alcohol. The other substances may be used alone or in combination of two or more.

[0077] The amount of other substances used is not particularly limited, but in the case of recycled fine powder, it is 30% by mass or less relative to the monomer, and in the case of other than fine powder, the total concentration of other substances is preferably 10% by mass or less relative to the monomer, more preferably 0.001% by mass or more and 5% by mass or less, and particularly preferably 0.01% by mass or more and 1% by mass or less.

[0078] (Polymerization initiator) The polymerization initiator used in the present invention is not particularly limited since it is appropriately selected depending on the polymerization form, etc., but examples thereof include a thermal decomposition type polymerization initiator, a photodecomposition type polymerization initiator, or a combination of these, or a redox type polymerization initiator combined with a reducing agent that promotes the decomposition of the polymerization initiator. In particular, a peroxide or an azo compound, more preferably a peroxide, and even more preferably a persulfate, are used. The amount of the polymerization initiator used is preferably 0.001 mol% or more and 1 mol% or less, more preferably 0.001 mol% or more and 0.5 mol% or less, based on the monomer. The amount of the reducing agent used is preferably 0.0001 mol% or more and 0.02 mol% or less, based on the monomer.

[0079] (Polymerization method) It is also preferable to reduce the dissolved oxygen in the aqueous monomer solution before polymerization by raising the temperature or replacing it with an inert gas. For example, the dissolved oxygen is preferably reduced to 5 ppm or less, more preferably 3 ppm or less, and particularly preferably 1 ppm or less. Also, air bubbles (particularly the above-mentioned inert gases, etc.) can be dispersed in the aqueous monomer solution. In this case, the polymerization reaction becomes foaming polymerization.

[0080] The polymerization form is not particularly limited. From the viewpoint of water absorption characteristics, ease of polymerization control, etc., preferable examples include droplet polymerization in a gas phase, aqueous solution polymerization, and reversed-phase suspension polymerization (here, droplet polymerization in a hydrophobic organic solvent is also included as an example of reversed-phase suspension), more preferably aqueous solution polymerization and reversed-phase suspension polymerization, and further preferably aqueous solution polymerization.

[0081] (Gel crushing process) This step is a step of pulverizing the hydrogel crosslinked polymer obtained in the polymerization step simultaneously with and / or after polymerization to obtain fine particles, for example, a step of pulverizing the hydrogel crosslinked polymer by a device such as a screw extruder such as a kneader or a meat chopper, a cutter mill, etc. to obtain a particulate hydrogel crosslinked polymer (hereinafter, "particulate hydrogel"). The preferred particle size is in the range described later, and the step is carried out so that the shape and size of the granular dried product obtained in the heat drying step described later or the post-crosslinked granular dried product obtained in the post-crosslinking step approach the desired product particle size.

[0082] In the gel pulverization, in (B), a used water absorbent resin or a solubilized material thereof is mixed with a monomer of a water absorbent resin or a solid content of a hydrous gel in the middle of production in an amount of 1 mass % or more and 60 mass % or less, further 3 mass % or more and 50 mass % or less, particularly 5 mass % or more and 40 mass % or less.

[0083] (4) Drying method of hydrogel In the method for producing a recycled water absorbent resin composition of the present invention, the hydrogel to be dried may be a hydrogel derived from a used water absorbent resin after purification, or a hydrogel obtained by using a used water absorbent resin after purification or a solubilized product thereof as a part of a raw material in a production process for a recycled water absorbent resin composition including a polymerization step of (B) an unsaturated monomer aqueous solution. These hydrogels are preheated to 40°C or higher, fluidized in a container rotary dryer or a fluidized dryer, and heated and dried under an air flow.

[0084] (drying temperature) In the heat drying method of the present invention, when a container rotary dryer is used, the temperature of the gas phase and / or the inner surface of the rotary container is preferably heated to 150° C. or higher, more preferably 180° C. or higher, and even more preferably 200° C. or higher. When a gas is introduced into the rotary container as a heat medium, the temperature of this gas is preferably lower than the temperature of the inner surface of the rotary container. The temperature of the airflow is preferably heated to 100° C. or higher. The upper limit temperature during drying is usually preferably 300° C. or lower, more preferably 250° C. or lower, from the viewpoint of coloring and deterioration of physical properties after drying.

[0085] (drying equipment) In the production method according to the present invention, the hydrogel is fluidized and dried in a container rotary dryer or a fluidized dryer. The drying may be a batch type, continuous type, or semi-continuous type.

[0086] The drying apparatus used in the present invention is not particularly limited as long as it has the function of fluidizing and drying the hydrous gel. As a means for fluidizing the hydrous gel, the material may be placed inside a rotating container as shown in FIG. 1 or FIG. 2 and then agitated and dried, or the material may be fluidized by hot air as in a fluidized bed as shown in FIG. 3, but a container rotary type dryer is preferably used. It is defined as a dryer equipped with a fluidizing means for fluidizing the material in the dryer (for example, agitating blades provided in the dryer or the rotation of the dryer itself) and one or more heating means. The agitation method and form are not particularly limited, and it is sufficient that the particulate hydrous gel in the drying apparatus is fluidized by agitating means such as an agitating blade or a rotating cylinder. Note that a method of stretching a material on a heating surface and drying it, such as a drum dryer, does not fall under the drying method of the present invention, since the particles are fixed to the dryer.

[0087] Also usable is a dryer (rotary dryer) in which the agitation means is a rotating cylinder, in which a cylindrical or other container that holds the material to be dried is rotated. Specific examples of the rotary dryer include a rotary dryer (Okawahara Manufacturing Co., Ltd.), a rotary kiln (Kurimoto Iron Works Co., Ltd.), and a steam tube dryer (Kurimoto Iron Works Co., Ltd., Ube Machinery Co., Ltd., Tsukishima Kikai Co., Ltd., and Mitsui Zosen Co., Ltd.).

[0088] A continuous agitator dryer that is not classified as a rotary dryer agitates materials with an agitator blade such as a paddle as shown in Fig. 4. This not only makes it disadvantageous in removing foreign matter by airflow, but also may cause deterioration of the physical properties of the water absorbent resin after drying and aggregation during drying.

[0089] Therefore, from the viewpoint of removing foreign matter and reducing mechanical damage to the water absorbent resin, a preferred dryer is a rotary dryer. From the viewpoint of reducing thermal and mechanical damage, a rotary dryer having a heating means selected from a ventilation heating type for direct heat transfer and an outer wall heating type and a tubular heating type for indirect heat transfer is more preferred. The tubular heating type is more preferred because it can increase the heat transfer area inside the dryer by using a large number of heating tubes, thereby enabling efficient drying. Examples of such rotary dryers include (heated tube-equipped) rotary dryers as shown in Figs. 1 and 2.

[0090] For example, this rotary dryer with heating tubes (FIG. 2) includes a rotating container that contains particulate hydrous gel and rotates as a main body, and a plurality of heating tubes that are located inside the rotating container, extend in the axial direction, and rotate together with the rotating container. More preferably, this rotary dryer includes another heating means on the outer circumferential surface of the rotating container. In this rotary dryer, the particulate hydrous gel contained in the rotating container is stirred by the rotation of the container and heated by contact with the plurality of heating tubes or by heat conduction from the heating tubes. The inner surface of the rotating container is also heated by radiant heat from the plurality of heating tubes, and if necessary, the hydrous gel is further heated by the heating means located on the outer circumferential surface of the rotating container. In this rotary dryer, other stirring means such as stirring blades are also used as necessary, but mainly, the particulate hydrous gel flows in the container due to the rotation of the rotating container that contains the hydrous gel, so that mechanical and thermal damage to the hydrous gel to be dried is small. As a result, foreign matter can be removed from the water-absorbent resin during drying by the rotation and airflow. In addition, the ventilated heating rotary kiln shown in Figure 1 has the advantage that foreign matter (especially pulp, which has a smaller specific gravity than absorbent resin) can be easily removed by scattering it due to the air flow.

[0091] As long as the object of the present invention is achieved, the number of agitation dryers that can be used in the heat drying step may be one or more than one. A combination of multiple dryers with different specifications may be used. When multiple dryers are used, the timing of switching can be determined using the solid content rate or the remaining solvent amount of the resulting granular dried product as an index. For example, when the solid content rate is used as an index, examples of the method include drying to a solid content of about 70% by mass in the first dryer, then switching to a second dryer to dry to a desired solid content rate, and further drying to a solid content of about 85% by mass in the second dryer, then switching to a third dryer to dry to a desired solid content rate.

[0092] In the manufacturing method according to the invention, when the agitation dryer (particularly the continuous agitation type) is a rotary dryer (where the main body itself rotates), from the viewpoint of drying efficiency, its Froude number (Fr=ω2×r / g) is appropriately set depending on the size of the device and the drying throughput (amount of drying per hour), but is preferably in the range of 0.001 to 1, more preferably 0.005 to 0.5, even more preferably 0.01 to 0.3, and particularly preferably 0.02 to 0.2. The Froude number Fr is the ratio of the centrifugal acceleration ω2×r acting on the material to be dried while being agitated in the rotating container to the gravitational acceleration g. (ω is the angular velocity of the rotor: rad / sec, and r is the representative radius of the rotor: m).

[0093] In the case of an agitation dryer, the rotation speed of the rotating shaft is set appropriately depending on the device, but it is preferable to set the rotation speed so that the Froude number Fr is within the above range. The specific rotation speed is usually in the range of 1 rpm to 10,000 rpm, more preferably 5 rpm to 500 rpm, and even more preferably 10 rpm to 300 rpm.

[0094] In the case of a rotary mixer in which the container that holds the material to be dried itself rotates, the rotation speed of the container is appropriately set depending on the size of the device and the drying processing amount (amount of drying per hour), but is preferably 1 rpm to 10,000 rpm, more preferably 1 rpm to 250 rpm, even more preferably 1 rpm to 100 rpm, and even more preferably 2 rpm to 50 rpm. The peripheral speed (peripheral speed (V) (m / s) = 2πr × n / 60) is not particularly limited, but is preferably 0.05 m / s to 10 m / s, more preferably 0.1 m / s to 8 m / s, and even more preferably 0.15 m / s to 5 m / s.

[0095] (air current) The above-mentioned agitation type drying device introduces an air current into the device. While the material to be dried is fluidized by the agitation drying, the air current can remove foreign matter (especially fine particles and particles with a light specific gravity) and dry the material. The carrier gas can be at room temperature if the inner wall of the drying container is heated, but it is preferably heated to 100°C or higher.

[0096] Also, a high-temperature moist mixed gas (hereinafter referred to as "humid mixed gas") can be used as the carrier gas. In the present invention, the moist mixed gas means a mixed gas containing water vapor. Preferably, the moist mixed gas is introduced into the stirring type drying device and circulated for use. The temperature of the airflow is preferably 105°C or higher, more preferably 120°C or higher, and even more preferably 140°C or higher. The upper limit is preferably 250°C or lower, more preferably 200°C or lower.

[0097] The dew point of the high humidity mixed gas is preferably 60°C or higher, more preferably 70°C or higher, even more preferably 80°C or higher, and particularly preferably 90°C or higher. In the present invention, the gas is introduced into a continuous stirring dryer from one or more locations, thereby adjusting the atmospheric dew point inside the drying apparatus. The dew point is measured at the time of exhaust from these dryers, and is preferably 60°C or higher, more preferably 65°C or higher, and even more preferably 70°C or higher. The upper limit is not particularly limited, but is preferably 100°C or lower. By setting the dew point within the above range, the drying state is improved, and coloration and residual monomers are reduced, and the performance of the obtained water absorbent resin is improved.

[0098] Examples of the carrier gas include air (including dry air), nitrogen, water vapor, and mixed gases thereof. From the viewpoint of ease of handling, dry air, nitrogen, water vapor, and mixed gases thereof are preferably used. The amount of the carrier gas introduced is arbitrarily set based on the amount of water evaporation per unit time and the desired properties of the exhaust gas (dew point, amount of volatile components, etc.). When a heated carrier gas is used, the gas also acts as a heat medium, further promoting drying. Preferably, nitrogen, water vapor, and mixed gases of these with air are used. When a mixed gas containing water vapor (hereinafter also referred to as a high-humidity mixed gas) is used, the inside of the drying device becomes a low-oxygen state, and oxidation and deterioration during drying are suppressed. As a result, it is possible to achieve improved performance and low coloration of the water-absorbent resin. Furthermore, it is preferable because it is possible to suppress aggregation and clumping of the hydrous gel during drying.

[0099] Conventionally, in order to suppress the deterioration of the physical properties and coloring of the water absorbing agent due to oxygen, it was necessary to dry the particulate hydrogel under an inert gas atmosphere such as nitrogen or argon, which caused an increase in costs. By introducing the high humidity mixed gas into the agitation type drying device, the inside of the drying device can be made into a low oxygen state even if the amount of inert gas used is reduced or even if no inert gas is used. As a result, the physical properties of the water absorbing agent are improved and coloring is suppressed. In addition, the increase in costs due to the use of inert gas is avoided. Furthermore, the introduction of the high humidity mixed gas is preferable because it also contributes to suppression of aggregation and / or clumping of the particulate hydrogel during drying.

[0100] The above-mentioned "low oxygen state" means a state in which the oxygen concentration in the agitation drying device is low, and particularly means a state in which the oxygen concentration in the atmosphere in the drying chamber in which the particulate hydrogel is stored is low. This oxygen concentration is preferably 15% by volume or less, more preferably 10% by volume or less, even more preferably 5% by volume or less, and particularly preferably 1% by volume or less. The lower limit is preferably 0% by volume, but may be about 0.1% by volume.

[0101] The continuous agitation dryer can also have a function of pressurizing, normal pressure, or reduced pressure inside the device. When the pressure is increased, the pressure is adjusted, for example, by increasing the amount of carrier gas introduced into the dryer. Preferably, the degree of pressurization relative to atmospheric pressure is a slight pressure of more than 0 kPa and not more than 0.01 kPa. When the pressure is reduced, the pressure is adjusted, for example, by changing the amount of exhaust gas (water vapor generated by drying and carrier gas introduced) from the dryer. The degree of reduced pressure relative to atmospheric pressure is preferably a slight pressure of more than 0 kPa and not more than 5 kPa, more preferably more than 0 kPa and not more than 2 kPa, and even more preferably 0.01 kPa or more and not more than 0.5 kPa. By applying a slight reduced pressure or slight pressurization, it is easier to remove foreign matter by the carrier gas (air flow), which is preferable.

[0102] The amount of gas introduced is usually 0.05 Nm3 per unit time of processing amount (kg / hr) calculated as solid content of particulate hydrogel. 3 / kg or more 20Nm 3 / kg or less, but preferably 0.1 Nm 3 / kg or more 10Nm 3 / kg or less, more preferably 0.1Nm 3 / kg or more 5Nm 3 / kg or less, more preferably 0.2 Nm 3 / kg or more 2.5Nm 3 / kg or less, particularly preferably 0.2 Nm 3 / kg or more 1Nm 3 / kg or less.

[0103] The direction of gas movement in the continuous agitation dryer may be parallel or countercurrent to the direction of movement of the particulate hydrogel to be dried, or a mixture of these.

[0104] (Removal of foreign matter by airflow) Furthermore, the airflow removes water-absorbent resin fine particles or foreign matter (such as low-density pulp). With this configuration, the amount of foreign matter is reduced, and coloring and performance degradation of the recycled water-absorbent resin caused by the foreign matter is further suppressed. The carrier gas removed by the airflow may be reused in the drying process after removing fine powder and foreign matter with a filter or mesh (wire screen), and then reheated as necessary.

[0105] (drying temperature) In addition, the drying temperature in the continuous stirring dryer is adjusted by the temperature of the heat medium used. For example, when the above-mentioned heated gas (hot air) is introduced into the inside of these dryers (the part containing the particulate hydrogel), the heating tube of a rotary dryer with a heating tube, or the jacket installed on the outer surface of the dryer, the temperature of the heat medium (gas) is preferably 150°C or higher (if the heat medium is steam, the saturation pressure is about 0.47MPa or higher), more preferably 160°C or higher (about 0.62MPa or higher), even more preferably 170°C or higher (about 0.79MPa or higher), and particularly preferably 180°C or higher (1.0MPa or higher). In addition, the drying temperature is preferably 300°C or lower, more preferably 280°C or lower, and even more preferably 250°C or lower for both direct and indirect heat transfer, from the viewpoint of deterioration and coloring of the water-absorbing resin and the performance of the water-absorbing agent. The temperature may be a constant temperature, or may be appropriately changed during drying. The drying time is preferably from 10 minutes to 120 minutes, more preferably from 20 minutes to 90 minutes, and even more preferably from 20 minutes to 60 minutes.

[0106] Furthermore, it is preferable that the temperature of the inner surface of the rotating vessel 10 is heated to the above temperature range (preferably 150° C. or higher) before the particulate hydrous gel is charged into the rotating vessel 10. This is preferable because it reduces adhesion of the particulate hydrous gel to the inner surface of the rotating vessel 10 and the heating tube 12, and also avoids a decrease in drying efficiency due to adhesion to the heating tube 12.

[0107] (chelating agent) In the drying step of the present invention, it is preferable that a chelating agent is further present. With this configuration, coloring and performance deterioration resulting from the used water absorbent resin or its solubilized product are further suppressed. The chelating agent is preferably contained in the hydrogel before drying, and the chelating agent may be added to the used water absorbent resin or its solubilized product, or the chelating agent may be added to the monomer in the polymerization step of the recycled water absorbent resin composition obtained by using the used water absorbent resin or its solubilized product as a part or all of the raw material, or to the hydrogel after polymerization. When the chelating agent is added after polymerization, it is also preferable to mix the chelating agent with the hydrogel before drying and mix the chelating agent uniformly by gel crushing.

[0108] The chelating agent to be used is preferably a polymeric compound or a non-polymeric compound, more preferably a non-polymeric compound, and is preferably a chelating agent containing an element other than carbon, hydrogen, and oxygen, more preferably nitrogen or phosphorus, in the molecule.

[0109] Specific examples of the chelating agent used in the present invention include hydroxy polycarboxylic acids, amino polycarboxylic acids, organic polyphosphates, inorganic polyphosphates, amino polyphosphates, and tropolone derivatives. At least one compound selected from the group consisting of these compounds is applied in the present invention. The above-mentioned "polyvalent" refers to having multiple functional groups in one molecule, preferably 2 to 30 functional groups, more preferably 3 to 20 functional groups, and even more preferably 4 to 10 functional groups.

[0110] From the viewpoint of the effect on polymerization and the physical properties of the resulting recycled water absorbent resin composition, the molecular weight of the chelating agent is preferably from 100 to 5000, more preferably from 200 to 1000. If the molecular weight exceeds 5000, the aqueous monomer solution may thicken depending on the timing of addition of the chelating agent, which is undesirable because it makes it difficult to control polymerization and mix uniformly.

[0111] Specific examples of the amino polycarboxylic acid include iminodiacetic acid, hydroxyethyliminodiacetic acid, nitrilotriacetic acid, nitrilotripropionic acid, ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, trans-1,2-diaminocyclohexanetetraacetic acid, N,N-bis(2-hydroxyethyl)glycine, diaminopropanoltetraacetic acid, ethylenediamine2propionic acid, N-hydroxyethylethylenediaminetriacetic acid, glycol ether diaminetetraacetic acid, diaminopropanetetraacetic acid, N,N'-bis(2-hydroxybenzyl)ethylenediamine-N,N'-diacetic acid, 1,6-hexamethylenediamine-N,N,N',N'-tetraacetic acid, and salts thereof.

[0112] Specific examples of the organic polyphosphate include nitriloacetic acid-di(methylenephosphinic acid), nitrilodiacetic acid-(methylenephosphinic acid), nitriloacetic acid-β-propionic acid-methylenephosphonic acid, nitrilotris(methylenephosphonic acid), and 1-hydroxyethylidene diphosphonic acid.

[0113] Specific examples of the inorganic polyphosphate include pyrophosphoric acid, tripolyphosphoric acid, and salts thereof.

[0114] Specific examples of the hydroxy polyvalent carboxylic acid include malic acid, citric acid, and salts thereof.

[0115] Specific examples of the amino polyphosphate include ethylenediamine-N,N'-di(methylenephosphinic acid), ethylenediaminetetra(methylenephosphinic acid), cyclohexanediaminetetra(methylenephosphonic acid), ethylenediamine-N,N'-diacetic acid-N,N'-di(methylenephosphonic acid), ethylenediamine-N,N'-di(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), polymethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), and salts thereof.

[0116] Specific examples of the tropolone derivative include tropolone, β-thujaplicin, and γ-thujaplicin.

[0117] Among these, chelating agents selected from amino polycarboxylic acids, organic polyphosphates, and amino polyphosphates are preferred, amino polycarboxylic acid-based chelating agents having three or more carboxyl groups are more preferred, and from the viewpoint of gel stability, diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, trans-1,2-diaminocyclohexanetetraacetic acid, and salts thereof are even more preferred.

[0118] In the present invention, the content (amount used) of the chelating agent is 0.001 parts by mass or more and 5 parts by mass or less, preferably 0.02 parts by mass or more and 1 part by mass or less, more preferably 0.03 parts by mass or more and 0.9 parts by mass or less, even more preferably 0.04 parts by mass or more and 0.8 parts by mass or less, still more preferably 0.05 parts by mass or more and 0.7 parts by mass or less, particularly preferably 0.06 parts by mass or more and 0.6 parts by mass or less, and most preferably 0.07 parts by mass or more and 0.5 parts by mass or less, relative to 100 parts by mass of the solid content of the water absorbent resin.

[0119] (reducing agent) In the present invention, it is preferable to further add a reducing agent, particularly a sulfur-based inorganic or organic reducing agent, during and / or after drying. With such a configuration, coloration and performance deterioration of the recycled water absorbent resin composition are further suppressed. In addition, the by-production of acrylamide in the recycled water absorbent resin composition can also be suppressed. The reducing agent is preferably contained in the hydrogel before drying, and the reducing agent may be added to the used water absorbent resin or its solubilized product, or the reducing agent may be added to the hydrogel after polymerization obtained in the polymerization step of the recycled water absorbent resin composition obtained by using the used water absorbent resin or its solubilized product as a part or all of the raw material. When the reducing agent is added after polymerization, it is also preferable to mix the reducing agent with the hydrogel before drying and mix the reducing agent uniformly by gel crushing.

[0120] The reducing agent is preferably a sulfur-based inorganic or organic reducing agent, and examples of such reducing agents include inorganic reducing agents such as sodium sulfite, potassium sulfite, calcium sulfite, ammonium sulfite, sulfurous acid, sodium hydrogen sulfite, potassium hydrogen sulfite, ammonium hydrogen sulfite, sodium thiosulfate, potassium thiosulfate, ammonium thiosulfate, and magnesium thiosulfate, and organic reducing agents such as 2-hydroxy-2-sulfinatoacetic acid, 2-hydroxy-2-sulfonatoacetic acid, cysteine, and cystine, and one or more of these can be used. Among these, sulfites and hydrogen sulfites are preferred in terms of effectiveness and cost.

[0121] In addition, the amount of the sulfur-containing reducing agent is preferably 0.05 parts by mass or more and 10 parts by mass or less, more preferably 0.1 parts by mass or more and 8 parts by mass or less, relative to 100 parts by mass of the solid content of the water absorbent resin. When the amount of the sulfur-containing reducing agent used is less than 0.05 parts by mass, the desired effect of reducing the residual monomer may not be obtained. When the amount of the sulfur-containing reducing agent used is more than 10 parts by mass, the amount of the agent is excessive for the required effect of reducing the residual monomer, which may lead to a decrease in physical properties, and is uneconomical in terms of cost. When the additive containing the sulfur-containing reducing agent is added in the form of an aqueous solution, the amount is preferably 0.001% by mass or more and 50% by mass or less relative to the aqueous solution. In the present invention, the additive is selectively and preferentially added to the surface of the particles and the fine particles, so a small amount is sufficient and the physical properties are not decreased.

[0122] (Moisture content of dried polymer) In the present invention, the moisture content of the dried polymer obtained through the heat drying step (sometimes referred to as drying step) is preferably in the range of 1% by mass to 20% by mass, more preferably 2% by mass to 15% by mass, and further preferably 3% by mass to 10% by mass. By setting the moisture content within this range, even if a used water absorbent resin or a solubilized product thereof is used as a part or all of the raw material, coloration of the dried polymer after drying can be suppressed.

[0123] (Particle size of dried polymer after drying) In the present invention, the particle size (particle size) of the dried polymer after drying (defined by sieve classification) is preferably 3 mm or less, more preferably 2 mm or less, and even more preferably 1 mm or less, for 60% by mass or more of the total amount of the dried polymer. With this configuration, foreign matter can be removed more efficiently. If the particle size is too large, foreign matter may be taken into the inside of the dried polymer, making it difficult to remove the foreign matter during or after drying (for example, removal of pulp derived from sanitary products by airflow or classification with a sieve, etc.).

[0124] (Cooling after drying) In order to solve the problems of the present invention, it is preferable to cool the dried polymer after the drying. The temperature of the dried polymer after cooling is preferably 100°C or less, more preferably 90°C or less, and even more preferably 85°C or less (the lower limit is 40°C or 50°C). If cooling is not performed, the dried polymer may be discolored or aggregated, and further, it may be difficult to control the particle size during pulverization. If pulverization is difficult, it may also be difficult to remove foreign matter during classification after pulverization (for example, removal during classification of pulp derived from sanitary products).

[0125] The cooling method is not particularly limited, but it is preferable to use a continuous cooler having a cooling means of ventilation heat transfer type or conductive heat transfer type, or a stirrer having a rotating shaft. A mixer having a function of ventilating an air current through the object to be cooled and cooling it is widely used as a cooler.

[0126] (5) Post-drying process (Crushing process, classification process) The dried polymer obtained after the drying may be subjected to a pulverization step or a classification step. By such a configuration, foreign matter can be removed, and in particular, by including a surfactant in the dried polymer, the amount of foreign matter such as pulp can be further reduced, and the water absorption performance can be further restored or improved.

[0127] In the present invention, from the viewpoint of water absorption performance and removal of foreign matter in classification, the mass average particle diameter of the water absorbent resin obtained through the classification step is preferably 200 μm to 600 μm, more preferably 250 μm to 550 μm, and even more preferably 300 μm to 500 μm. From the viewpoint of the quality of the obtained recycled water absorbent resin composition, it is preferable that the recycled water absorbent resin composition is mainly composed of particles having a particle diameter of 150 μm to 850 μm as defined by sieve classification. The ratio of particles having a particle diameter of 150 μm to 850 μm in the recycled water absorbent resin composition is preferably 90% by mass to 100% by mass, more preferably 95% by mass to 100% by mass, even more preferably 97% by mass to 100% by mass, and particularly preferably 99% by mass to 100% by mass. Therefore, the proportion of water-absorbent resin particles having particle sizes of less than 150 μm and more than 850 μm as determined by sieve classification is preferably 10 mass % or less, more preferably 5 mass % or less, further preferably 3 mass % or less, and particularly preferably 1 mass %.

[0128] (Surface crosslinking process) This step is a step of adding a surface crosslinking agent that reacts with the functional group (particularly carboxyl group) of the water-absorbent resin to the hydrogel after polymerization or its dried polymer to cause a crosslinking reaction. The crosslinking reaction is also called surface crosslinking or secondary crosslinking because crosslinking mainly occurs from the surface of the water-absorbent resin. In the production method according to the present invention, a surface crosslinking agent is added to the water-absorbent resin after the pulverization or classification during or after drying, particularly after drying, to cause a reaction. The surface crosslinking step includes a step of adding a surface crosslinking agent and a heat treatment step, and may include a cooling step after the heat treatment step as necessary.

[0129] In the present invention, as the surface crosslinking agent, a surface crosslinking agent capable of reacting with a plurality of functional groups (preferably a plurality of carboxyl groups) of the water-absorbing resin, preferably a surface crosslinking agent capable of covalent bonding or ionic bonding, further a surface crosslinking agent capable of covalent bonding, is used.Specific examples thereof include polyhydric alcohol compounds such as ethylene glycol, diethylene glycol, propylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, 1,3-propanediol, 2-butene-1,4-diol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol; epoxy compounds such as ethylene glycol diglycidyl ether and polyethylene glycol diglycidyl ether; alkylene carbonate compounds such as 1,3-dioxolane-2-one and 4-methyl-1,3-dioxolane-2-one; and the like.

[0130] The amount of the surface cross-linking agent added is preferably 5% by mass or less, more preferably 3% by mass or less, and further preferably 2% by mass or less, based on the solid content of the water absorbent resin during or after drying. The lower limit is preferably 0.001% by mass.

[0131] The surface cross-linking agent may be added as it is, but is preferably added in a solution state dissolved in water or an organic solvent for ease of addition. The concentration of the surface cross-linking agent solution is preferably 1% by mass or more, more preferably 2% by mass or more. The total amount of the solvent selected from water and an organic solvent is preferably 0% by mass or more and 10% by mass or less, more preferably 0.1% by mass or more and 8% by mass or less, and even more preferably 0.5% by mass or more and 5% by mass or less, based on the solid content of the water absorbent resin. When water and an organic solvent are used in combination, it is preferable that water is the main component.

[0132] The water-absorbent resin containing the surface cross-linking agent is heated to 100°C or higher to obtain a surface-cross-linked water-absorbent resin. The preferred maximum temperature varies depending on the type of surface cross-linking agent, but is preferably 100°C or higher and 250°C or lower, more preferably 120°C or higher and 230°C or lower, and even more preferably 150°C or higher and 210°C or lower. The time of the heat treatment step may be appropriately set based on the water content of the water-absorbent resin, the type of the surface cross-linking agent, the thermal efficiency of the heating device, and the like. As a rough guide, heating may be performed until the water content becomes 10% by mass or lower, and the time is in the range of 10 minutes to 120 minutes, preferably 30 minutes to 90 minutes. After the surface cross-linking, the reaction may be stopped by cooling as desired.

[0133] (Other processes) The manufacturing method according to the present invention may also include, as other steps, a step of adding additives such as inorganic fine particles, dust inhibitors, fungicides, antibacterial agents, antioxidants, ultraviolet absorbers, colorants, fragrances, deodorants, and organic fibrous materials before or after drying. When these additives are added, the content (mass%) of the additives is preferably 0.001% by mass or more and 10% by mass or less, more preferably 0.01% by mass or more and 5% by mass or less, still more preferably 0.05% by mass or more and 1% by mass or less, and particularly preferably 0.1% by mass or more and 0.5% by mass or less, based on the mass of the water absorbent resin. Specific examples of the inorganic fine particles include minerals such as hydrotalcite; silicon oxide, titanium oxide, and aluminum oxide.

[0134] (6) Properties of Recycled Water-Absorbent Resin Composition The recycled water-absorbent resin composition obtained above has less coloring and foreign matter, and can be used in a wider range than conventional recycled water-absorbent resin compositions. The recycled water-absorbent resin composition obtained has the following properties:

[0135] The YI value (Yellow-Index) of the recycled water absorbent resin composition of the present invention is preferably not more than 20, more preferably not more than 15. By virtue of this constitution, the substantially white recycled water absorbent resin composition can be used in a wider range of applications.

[0136] The residual monomer content of the recycled water absorbent resin composition of the present invention is preferably 300 ppm or less, more preferably 200 ppm or less, and further preferably 100 ppm or less. With such a constitution, the recycled water absorbent resin composition can be used in a wider range of applications, and the by-production of acrylamide can be suppressed.

[0137] The amount of magnesium and calcium contained in the recycled water absorbent resin composition of the present invention is preferably 1 ppm or more and 1000 ppm or less. With this constitution, the recycled water absorbent resin composition can suppress the performance degradation and can be used in a wider range.

[0138] The amount of urea and ammonia contained in the recycled water absorbent resin composition of the present invention is preferably 4 mass % or less, more preferably 3 mass % or less, further preferably 2 mass % or less, and particularly preferably 1 mass %. With such a constitution, the performance deterioration of the recycled water absorbent resin composition can be suppressed, and it can be used in a wider range.

[0139] The amount of foreign matter (typified by pulp) contained in the recycled water absorbent resin composition of the present invention is preferably 1 mass % or less, more preferably 0.5 mass % or less, and further preferably 0.1 mass % or less.

[0140] The recycled water absorbent resin composition of the present invention has a high water absorption capacity (high CRC) even though it is made of a used water absorbent resin or its solubilized product as a part or all of the raw material. The CRC is preferably 15 g / g or more, more preferably 25 g / g or more. There is no particular restriction on the upper limit, and a higher CRC is preferable, but from the viewpoint of the balance with other physical properties, it is preferably 70 g / g or less, more preferably 50 g / g or less, and even more preferably 40 g / g or less.

[0141] The recycled water absorbent resin composition of the present invention has a high water absorption capacity under pressure (high AAP) even though used water absorbent resin or its solubilized product is used as a part or all of the raw material. The AAP is preferably 15 g / g or more, more preferably 20 g / g or more, even more preferably 22 g / g or more, particularly preferably 23 g / g or more, and most preferably 24 g / g or more. The upper limit is not particularly limited, but is preferably 30 g / g or less.

[0142] The recycled water absorbent resin composition of the present invention has a low water-soluble content, even though it is made of a used water absorbent resin or a solubilized product thereof as a part or all of the raw material. The water-soluble content is usually 50 mass % or less, preferably 35 mass % or less, more preferably 25 mass % or less, and further preferably 15 mass % or less.

[0143] The water content of the recycled water absorbent resin composition of the present invention is preferably more than 0 mass% and not more than 20 mass%, more preferably 1 mass% or more and 15 mass% or less, even more preferably 2 mass% or more and 13 mass% or less, and particularly preferably 2 mass% or more and 10 mass% or less.

[0144] The particle size of the recycled water-absorbent resin composition of the present invention is preferably within the above range.

[0145] (7) Uses of the recycled water-absorbent resin composition The use of the recycled water absorbent resin composition obtained by the present invention is not particularly limited, but it is preferably used as an absorbent material for absorbent articles such as paper diapers, sanitary napkins, incontinence pads, etc. In particular, it can be used as an absorbent material for high-concentration paper diapers, which have been problematic in terms of odor, coloration, etc. derived from raw materials.

[0146] The present invention may also include the following inventions [1] to

[15] . [1] A method for producing a recycled water absorbent resin composition using a used water absorbent resin or a solubilized product thereof as a part or all of a raw material, (A) a drying step of a hydrogel crosslinked polymer derived from a used water absorbent resin after purification, or (B) In a manufacturing process of a recycled water-absorbent resin composition including a polymerization process of an unsaturated monomer aqueous solution, in a drying process of a hydrogel-like crosslinked polymer obtained by using a purified used water-absorbent resin or a solubilized product thereof as a part of a raw material, A method for producing a regenerated water-absorbent resin, comprising fluidizing the hydrogel-like crosslinked polymer, which has been preheated to 40°C or higher, in a container rotary dryer or a fluidized bed dryer, and drying the polymer by heating under an air stream. [2] The method according to [1], wherein the hydrogel crosslinked polymer contains a surfactant or a crosslinking agent that reacts with a carboxyl group. [3] The method according to [1] or [2], wherein a chelating agent is further added to the hydrous gel-like crosslinked polymer in the drying step. [4] The method according to any one of [1] to [3], wherein the hydrogel crosslinked polymer is dried by heating to obtain a dried polymer having a water content of 3% by mass or more and 20% by mass or less. [5] The method according to any one of [1] to [4], further comprising adding a reducing agent to the hydrogel-like crosslinked polymer and / or the dried polymer before and / or after the drying step. [6] The method according to any one of [1] to [5], wherein finely divided dry polymer particles are removed from the air stream. [7] The method according to any one of [1] to [6], wherein the oxygen concentration inside a dryer used in the drying step is 15% by volume or less. [8] The method according to any one of [1] to [7], wherein 60% by mass or more of the dried polymer obtained after the drying step has a particle size of 3 mm or less. [9] A gel crushing step is included before the drying step, The method according to any one of [1] to [8], wherein in the gel-crushing step, the hydrogel crosslinked polymer is gel-crushed into particles having an average particle size of 3 mm or less.

[10] The method according to any one of [1] to [9], wherein the airflow has a temperature of 100° C. or higher.

[11] The method according to any one of [1] to

[10] , wherein the drying is carried out in a rotary container dryer having an inner wall temperature of 150° C. or higher.

[12] The method according to any one of [1] to

[11] , further comprising, after the drying step, a step of pulverizing the dried polymer, and then a step of classifying the same.

[13] The method according to any one of [1] to

[12] , wherein the used water absorbent resin or a solubilized product thereof contains magnesium and calcium in an amount of 1 ppm or more and 1000 ppm or less.

[14] The method according to any one of [1] to

[13] , wherein the recycled water-absorbent resin composition has a YI value of 20 or less.

[15] The method according to any one of [1] to

[14] , wherein the recycled water absorbent resin composition has a residual monomer content of 300 ppm or less.

[16] A recycled water-absorbent resin composition obtained by the production method according to any one of the above [1] to

[15] . EXAMPLES

[0147] The present invention will be described in more detail with reference to the following examples and comparative examples, but the present invention is not limited to these examples, and examples obtained by appropriately combining the technical means disclosed in each example are also included in the scope of the present invention. Unless otherwise noted, measurements were taken at room temperature (20°C or higher and 25°C or lower) and at a relative humidity of 50±5% RH. For convenience, "liter" may be expressed as "l" or "L," and "mass%" may be expressed as "wt%."

[0148] (Measurement and evaluation methods) The methods for measuring and evaluating the various physical properties in the examples and comparative examples are as follows.

[0149] (a) Water soluble content The water-soluble content of the water-absorbent resin was measured and determined by the following method.

[0150] 200.0 g of 0.90% by mass sodium chloride aqueous solution was weighed out into a 250 ml glass container containing a cylindrical rotor with a length of 35 mm and a cross-sectional diameter of 7.5 mm, and then 1.00 g of water-absorbing resin was added to the sodium chloride aqueous solution, and the container was covered with plastic wrap. After that, the aqueous solution to which the water-absorbing resin was added was stirred (rotation speed: 500 rpm) at room temperature for 16 hours using the cylindrical rotor. By this operation, the water-soluble components in the water-absorbing resin were extracted.

[0151] After stirring, the aqueous solution, which was the extract, was filtered using a sheet of filter paper (manufactured by ADVANTEC Toyo Co., Ltd., product name: JIS P3801, No. 2 / thickness 0.26 mm, retention particle size 5 μm), and 50.0 g of the resulting filtrate was used as the measurement liquid.

[0152] Next, the measurement solution was titrated with a 0.1N-NaOH aqueous solution until the pH reached 10, and then titrated with a 0.1N-HCl aqueous solution until the pH reached 2.7. The titration amounts at this time were calculated as [NaOH] ml and [HCl] ml, respectively.

[0153] In addition, the same procedure was carried out without adding any water-absorbent resin, using only 200.0 g of a 0.90% by mass aqueous sodium chloride solution, to determine the blank titration amount ([bNaOH] ml and [bHCl] ml).

[0154] The water-soluble content was calculated from the titer and the average molecular weight of the monomer according to the following formula (1). Water soluble content (mass%) = 0.1 × average molecular weight of monomer × 200 × 100 × ([HCl]-[bHCl]) / 1000 / 1.0 / 50.0 / (solid content concentration of water absorbent resin) / 100) Equation (1)

[0155] When the monomer average molecular weight was unknown, it was calculated using the neutralization ratio calculated by the following formula (2). Neutralization rate (mol%) = {1 - ([NaOH] - [bNaOH]) / ([HCl] - [bHCl])} × 100 Equation (2)

[0156] (b) CRC The "CRC" of a water-absorbent resin is an abbreviation for "Centrifuge Retention Capacity" and indicates the absorption capacity (unit: g / g) of a water-absorbent resin for 30 minutes under no pressure with respect to a 0.90% by mass aqueous sodium chloride solution. A specific method for measuring the CRC of a water-absorbent resin (recycled water-absorbent resin composition) is as follows.

[0157] 0.200 g of the water-absorbent resin was uniformly placed in a bag (85 mm x 60 mm) made of nonwoven fabric (manufactured by Nangoku Pulp Kogyo Co., Ltd., product name: Heatlon Paper, model: GSP-22) and heat-sealed. The bag (containing the water-absorbent resin) was immersed in a large excess (usually about 500 ml) of 0.90% by mass sodium chloride aqueous solution at room temperature. After 30 minutes, the bag was pulled out and drained for 3 minutes at a centrifugal force (250 G) described in ERT441.2-02 using a centrifuge (manufactured by Kokusan Co., Ltd., centrifuge: model H-122), and the mass W1 (g) of the bag was measured. In addition, the same operation was performed without using the water-absorbent resin, and the mass W0 (g) at that time was measured. From the obtained values ​​of W1 and W0, the CRC of the control water-absorbent resin was calculated according to the following formula (3): CRC of water-absorbent resin (g / g) = (W1-W0) / (mass of water-absorbent resin)-1···Equation (3).

[0158] (c) AAP0.3 The "AAP" of a water-absorbent resin is an abbreviation for "Absorption Against Pressure" and indicates the absorbency (unit: g / g) against a 0.90% by mass aqueous sodium chloride solution. Also, "AAP0.3" means the AAP under a pressure of 0.3 psi.

[0159] The AAP0.3 of the above water absorbent resin (regenerated water absorbent resin composition) was measured in accordance with ERT442.2-02. Specifically, 0.9 g of the water absorbent resin was placed in a large excess of 0.9 mass % sodium chloride aqueous solution for 1 hour, and the AAP0.3 was measured at 2.07 kPa (21 g / cm 2 The value was measured after swelling under a pressure of 0.5 psi (0.3 psi).

[0160] (d) Color evaluation (yellowness index / YI value) The color evaluation of the water-absorbent resin was performed using a spectrophotometer (Spectrophotometer SE7700) manufactured by Nippon Denshoku Industries Co., Ltd. Reflection measurement was selected as the measurement setting condition, and the measurement diameter was LAV (28 mm). In addition, the attached 35Φ×15H round cell, 35Φ×15H cell case, and standard white plate for powder were used. The YI value (Yellow Index) was measured with the above spectrophotometer under the conditions of room temperature (20℃ to 25℃) and humidity of 50RH%.

[0161] (e) Residual monomer content (residual acrylic acid content) The amount of residual monomers in the water absorbent resin was quantified according to ERT410.2-02 (Residual Monomers).

[0162] Specifically, 1.0 g of the water absorbent resin was placed in 200 cm3 of a 0.90 mass% sodium chloride aqueous solution (temperature: 23±2°C), stirred at 500±50 rpm for 1 hour, and then filtered. The amount of residual monomer in the obtained filtrate was measured by HPLC.

[0163] (f) Solid content concentration / moisture content A water-absorbent resin (hydrated gel) having a mass Wa (g) was placed on an aluminum plate having a mass Wb (g) and dried in a hot air circulating oven at 180° C. for 3 hours. Thereafter, the total mass Wc (g) of the water-absorbent resin (hydrated gel) and the aluminum plate was measured. From the obtained values ​​of Wa, Wb, and Wc, the solid content concentration of the water-absorbent resin (hydrated gel) was calculated according to the following formula (4): Solids concentration (mass%) of water-absorbent resin (hydrated gel) = {(Wc - Wb) / Wa} × 100 Equation (4).

[0164] The water content of the water-absorbent resin (hydrous gel) is calculated according to the following formula (5): Water content (mass%) of water-absorbent resin (water-containing gel) = 100 – (solids concentration of water-absorbent resin (water-containing gel)) Equation (5).

[0165] [Reference example 1] 200 g of artificial urine (1.9 mass% urea, 0.80 mass% sodium chloride, 0.10 mass% magnesium chloride hexahydrate, 0.10 mass% calcium chloride dihydrate, 97.1 mass% ion-exchanged water) was poured into one commercially available disposable diaper to serve as a model for a sanitary product containing used water-absorbent resin.

[0166] In addition, the commercially available paper diaper has an absorbent layer made of a blend of approximately 11 g of absorbent resin and approximately 11 g of fluff pulp, and the absorbent resin used in the absorbent layer was a polyacrylic acid sodium salt-based absorbent resin with a absorption capacity (CRC) of 37 g / g.

[0167] Next, in order to separate the used water-absorbent resin contained in the paper diaper, the paper diaper was cut into pieces of several centimeters, and then a large excess of water was added and stirred to obtain an aqueous dispersion containing pulp, nonwoven fabric, thermoplastic binder, and used water-absorbent resin in a hydrogel state (hereinafter referred to as "hydrogel") (Reference 1).

[0168] Next, calcium chloride was added to the aqueous dispersion, causing the hydrogel (Reference 1) to shrink to a size of 1 mm or less and settle. The pulp, nonwoven fabric, and thermoplastic binder floating in the water were separated and removed based on the difference in specific gravity, and the hydrogel (Reference 1) that had shrunk and settled due to calcium chloride and the pulp with a light specific gravity were further filtered through a wire mesh to separate the hydrogel (Reference 1). The hydrogel (Reference 1) after separation contained a small amount of pulp derived from paper diapers as a foreign matter.

[0169] [Reference example 2] Hydrochloric acid was added to the hydrogel (Reference 1) obtained in Reference Example 1 to remove calcium, and an acid-type polyacrylic acid-based water-absorbent resin was obtained. Thereafter, the hydrogel (Reference 2) of a polyacrylic acid sodium salt-based water-absorbent resin was obtained by neutralizing the hydrogel with a 48% by mass aqueous solution of sodium hydroxide. A small amount of pulp derived from paper diapers was contained in the hydrogel (Reference 2) as a foreign matter.

[0170] [Reference example 3] In Reference Example 1, instead of calcium chloride, hydrogen peroxide was added in an amount of 5% by mass relative to the water absorbent resin, and the used water absorbent resin was dissolved by heating to 60° C. Then, the mixture was filtered to obtain a solubilized hydrogel (Reference 3) (solubilized product of used water absorbent resin). The hydrogel (Reference 3) after filtration contained a small amount of pulp derived from paper diapers as a foreign matter.

[0171] [Reference example 4] The hydrogel (Reference 1) obtained in Reference Example 1 was placed in a reaction vessel equipped with an agitator, and 306 parts by mass of a 3.0% by mass aqueous citric acid solution was added per 100 parts by mass of water absorbent resin (2.78 parts by mass of water absorbent resin solid content), followed by stirring for 15 minutes (dehydration treatment). Thereafter, the content of the reaction vessel was filtered through a 100-mesh stainless steel wire screen, and the filtrate was returned to the reaction vessel.

[0172] Next, 222 parts by mass of deionized water was added to the reaction vessel containing the filtrate and stirred for 15 minutes (cleaning treatment), after which the content of the reaction vessel was filtered through a 100-mesh stainless steel wire screen.

[0173] Thereafter, 1.98 parts by mass of a 45% by mass aqueous solution of sodium hydroxide was added dropwise as a neutralizing agent while stirring the contents of the reaction vessel. Thus, a hydrogel (Reference 4) was obtained. The hydrogel (Reference 4) after separation contained a small amount of pulp derived from paper diapers as a foreign matter.

[0174] [Production Example 1] A reaction vessel was charged with 244.9 g of acrylic acid, 0.71 g (0.040 mol % relative to the carboxyl group-containing unsaturated monomer) of polyethylene glycol diacrylate (molecular weight 523) as an internal crosslinking agent, 103.7 g of a 48.5 mass % aqueous sodium hydroxide solution, and 237.7 g of deionized water, and mixed to prepare an aqueous monomer solution (S1').

[0175] Next, the monomer aqueous solution (S1') was cooled while stirring. When the liquid temperature reached 40.0°C, 100.9 g of a 48.5 mass% aqueous sodium hydroxide solution adjusted to 40°C was added and mixed to prepare a monomer aqueous solution (S1). At this time, the temperature of the monomer aqueous solution (S1) rose to 78.1°C due to the heat of neutralization in the second stage immediately after preparation. Immediately after starting to mix the 48.5 mass% aqueous sodium hydroxide solution, precipitates were observed, but they gradually dissolved and became a transparent homogeneous solution.

[0176] Next, 12.1 g of a 4.0% by mass aqueous solution of sodium persulfate was added to the stirred monomer aqueous solution (S1), and the mixture was immediately poured into a stainless steel vat-type container in an open-air system. The time from the start of the second neutralization to the pouring of the monomer aqueous solution (S1) into the vat-type container was 55 seconds, and the vat-type container was a hot plate, which was heated until the surface temperature reached 40°C after the monomer aqueous solution (S1) was poured. The polymerization reaction started 70 seconds after the monomer aqueous solution (S1) was poured into the vat-type container. The polymerization reaction proceeded while the reactants expanded and foamed in all directions while generating water vapor. After the reaction, the reactants shrunk to a size slightly larger than the vat-type container. The reactants were taken out as a hydrous gel (S1) 3 minutes after the start of the polymerization reaction. The series of operations was carried out in an open-air system.

[0177] The hydrogel (S1) obtained by the polymerization reaction was cut into strips and crushed with a meat chopper having a die diameter of 7.5 mm to obtain a particulate hydrogel (S1).

[0178] [Production Example 2] In Production Example 1, the same operation as in Production Example 1 was performed except that the hydrogel (Reference 3) obtained in Reference Example 3 (solubilized material of used water absorbent resin) (10 mass% based on the solid content of the monomer) was added when preparing the monomer aqueous solution (S1'), thereby obtaining a hydrogel (S2) containing a solubilized material of used water absorbent resin.

[0179] [Example 1] To the hydrogel (S2) obtained in Production Example 2, 0.15% by mass of lauryl dimethylaminoacetate betaine was added as a surfactant based on the water-absorbent resin solid content, and then a particulate hydrogel (1) having an average particle size of about 1 mm was obtained using a meat chopper. Both the hydrogel (S2) and the particulate hydrogel (1) were kept at about 60°C (gel temperature).

[0180] Next, the particulate hydrogel (1) was agitated and dried under airflow for about 50 minutes using a rotary agitation type drying apparatus (see FIG. 2) equipped with a heating tube.

[0181] The rotary agitation type drying apparatus is equipped with a cylindrical rotating vessel (volume 100 L) having ten heating tubes extending in the direction of the rotation axis and two barriers (doughnut-shaped partition plates with one circular opening in the center, opening rate 50%). In addition, there is a downward inclination (0.6°) from the input part to the discharge part. Furthermore, at the end of the rotary vessel on the discharge part side, there is a doughnut-shaped partition plate (also called a discharge weir) with one circular opening (opening rate 24%) in the center.

[0182] In the drying in Example 1, steam of 2.7 MPa (temperature 228.1 ° C.) was introduced into each heating tube, and the inside of the rotating container (specified by a contact thermometer) was heated to 200 ° C. in advance, and the outer wall of the rotating container was also sufficiently heated by a tress. Drying was performed for 50 minutes by rotating the rotating container so that the Fried number Fr was 0.07. During drying, the supply amount and exhaust amount of air (air flow 140 ° C.) were adjusted so that the pressure difference between the inside of the rotating container and the outside air was -20 Pa and the exhaust dew point was 90 ° C. The air flow discharged from the drying device was passed through a filter to remove scattered particles, and then reheated to 140 ° C. and recycled to the drying device.

[0183] The dried polymer after drying was in the form of particles of about 1 mm to 2 mm, which were further crushed and classified using JIS standard sieves with mesh sizes of 850 μm and 150 μm to obtain an irregularly crushed recycled water absorbent resin composition (1). The physical properties of the recycled water absorbent resin composition (1) are shown in Table 1.

[0184] [Comparative Example 1] A recycled water-absorbent resin composition (C1) was obtained by the same procedure as in Example 1, except that the drying device was changed to a paddle dryer (without airflow) (see FIG. 4). The physical properties of the recycled water-absorbent resin composition (C1) are shown in Table 1.

[0185] [Comparative Example 2] The same operation as in Example 1 was carried out, except that the drying apparatus was a band drying model and the drying was performed by static drying at 180°C with hot air (see FIG. 6), to obtain a recycled water absorbent resin composition (C2). The physical properties of the recycled water absorbent resin composition (C2) are shown in Table 1.

[0186] [Comparative Example 3] A recycled water-absorbent resin composition (C3) was obtained by the same procedure as in Example 1, except that the temperature of the particulate hydrogel (1) was changed to 25° C. The physical properties of the recycled water-absorbent resin composition (C3) are shown in Table 1.

[0187] [Comparative Example 4] A recycled water absorbent resin composition (C4) was obtained by carrying out the same operation as in Example 1, except that drying was carried out without supplying an air flow of 140° C. to the rotary agitation type drying apparatus. The physical properties of the recycled water absorbent resin composition (C4) are shown in Table 1.

[0188] [Example 2] A recycled water-absorbent resin composition (2) was obtained by the same procedure as in Example 1, except that 0.1% by mass (based on solid content) of a chelating agent was added to the particulate hydrogel (1), mixed, and dried by stirring. The physical properties of the recycled water-absorbent resin composition (2) are shown in Table 1.

[0189] [Example 3] A recycled water-absorbent resin composition (3) was obtained by the same procedure as in Example 1, except that 0.1% by mass (based on solid content) of an inorganic reducing agent (sodium sulfite) was added to the particulate hydrogel (1), mixed, and dried by stirring. The physical properties of the recycled water-absorbent resin composition (3) are shown in Table 1.

[0190] [Table 1]

[0191] [Example 6] A recycled water-absorbent resin composition (6) was obtained by the same procedure as in Example 1, except that the hydrogel (Reference 1) (gel temperature 60° C.) obtained in Reference Example 1 was dried. The physical properties of the recycled water-absorbent resin composition (6) are shown in Table 2.

[0192] [Example 7] A recycled water-absorbent resin composition (7) was obtained by the same procedure as in Example 1, except that the hydrogel (Reference 2) (gel temperature 60° C.) obtained in Reference Example 2 was dried. The physical properties of the recycled water-absorbent resin composition (7) are shown in Table 2.

[0193] [Example 8] A recycled water-absorbent resin composition (8) was obtained by carrying out the same operation as in Example 1, except that the hydrogel (Reference 3) (gel temperature 60° C.) obtained in Reference Example 3 was used instead. The physical properties of the recycled water-absorbent resin composition (8) are shown in Table 2.

[0194] [Example 9] The same procedure as in Example 1 was carried out except that the hydrogel (Reference 4) (gel temperature 60° C.) obtained in Reference Example 4 was dried to obtain a recycled water-absorbent resin composition (9). The physical properties of the recycled water-absorbent resin composition (9) are shown in Table 2.

[0195] [Comparative Example 5] A recycled water absorbent resin composition (C5) was obtained by the same procedure as in Example 6, except that the drying apparatus was a band drying model and static drying was performed at 180°C (see FIG. 6) for 30 minutes. The physical properties of the recycled water absorbent resin composition (C5) are shown in Table 2.

[0196] [Table 2]

[0197] (summary) From Tables 1 and 2, it is seen that discoloration and residual monomers can be reduced by fluidizing the hydrogel, which has been heated to 40°C or higher in advance, in a container rotation type dryer or a fluidized dryer and drying it by heating under an air flow. From Examples 2 and 3, it is seen that discoloration and residual monomers can also be reduced by using specific additives (chelating agents, reducing agents) in the drying process.

[0198] In addition, the airflow (hot air) during the stirring and drying in the above-mentioned embodiment contains pulp scattered from the particulate hydrogel being stirred, and by using a filter when circulating the hot air from the drying device, foreign matter such as pulp with a light specific gravity scattered from the dried polymer after drying can be removed.

[0199] In contrast to the agitation drying in the embodiment (pulp is scattered by the air current from the flowing particulate hydrogel), in the static drying in the comparative example, the particulate hydrogel is layered in thickness and dried, so there is substantially no scattering of pulp in the hot air, and foreign matter (e.g. pulp) cannot be removed during drying. Pulp from the sanitary goods is easily mixed into the used water absorbent resin separated from the sanitary goods, but in this case, it is possible to remove foreign matter by agitating and drying the particulate hydrogel. [Industrial Applicability]

[0200] The method of the present invention provides a method for obtaining a regenerated water absorbent resin with less foreign matter, coloration, and residual monomers and with less deterioration, from a used water absorbent resin, without excessively consuming resources in recycling, and therefore contributes to the environment and resource saving and expands the possibility of recycling the water absorbent resin.

Claims

1. A method for producing a recycled water-absorbent resin composition using a used water-absorbent resin or a solubilized product thereof as a part or all of a raw material, (A) a step of drying a hydrogel crosslinked polymer derived from a used water absorbent resin after purification, or (B) In a manufacturing process of a recycled water-absorbent resin composition including a polymerization process of an unsaturated monomer aqueous solution, in a drying process of a hydrogel-like crosslinked polymer obtained by using a purified used water-absorbent resin or a solubilized product thereof as a part of a raw material, The method for producing a recycled water-absorbent resin comprises fluidizing the hydrogel crosslinked polymer, which has been preheated to 40°C or higher, in a container rotary dryer or a fluidized bed dryer, and drying the polymer by heating under an air stream.

2. 2. The method according to claim 1, wherein the hydrogel crosslinked polymer contains a surfactant or a crosslinking agent that reacts with a carboxyl group.

3. The method according to claim 1, wherein a chelating agent is further added to the hydrogel crosslinked polymer in the drying step.

4. The method according to claim 1 , wherein the hydrogel crosslinked polymer is heated and dried to obtain a dried polymer having a water content of 3% by mass or more and 20% by mass or less.

5. The method according to claim 1, wherein a reducing agent is further added to the hydrogel-like crosslinked polymer and / or the dried polymer before and / or after the drying step.

6. The process of claim 1 wherein particulate dry polymer is removed from the air stream.

7. 2. The method according to claim 1, wherein the oxygen concentration inside the dryer used in the drying step is 15% by volume or less.

8. The method according to claim 1, wherein 60% by mass or more of the dried polymer obtained after the drying step has a particle size of 3 mm or less.

9. A gel crushing step is included before the drying step, The method according to claim 1, wherein in the gel-crushing step, the hydrogel crosslinked polymer is gel-crushed into particles having an average particle size of 3 mm or less.

10. The method according to claim 1, wherein the airflow has a temperature of 100°C or higher.

11. 2. The method according to claim 1, wherein the drying is carried out in a rotary container dryer having an inner wall temperature of 150°C or higher.

12. The method of claim 1, further comprising the step of crushing the dried polymer after the drying step, followed by a classification step.

13. The method according to claim 1, wherein the used water absorbent resin or the solubilized product thereof contains magnesium and calcium in an amount of 1 ppm or more and 1000 ppm or less.

14. The method according to claim 1, wherein the recycled water-absorbent resin composition has a YI value of 20 or less.

15. The method according to claim 1, wherein the recycled water-absorbent resin composition has a residual monomer content of 300 ppm or less.

16. A recycled water-absorbent resin composition obtained by the manufacturing method according to any one of claims 1 to 15.

Citation Information

Patent Citations

  • Method and system for recovering pulp fibers and highly water-absorbent polymer from used absorbent articles

    WO2019087485A1

  • Method for regenerating highly water-absorbing polymer, method for producing highly water-absorbing recycled polymer, and use of alkali metal ion source

    WO2019151538A1

  • Method for producing water-absorbing resin particles

    WO2020213298A1

  • Method for recycling superabsorbent polymer derived from used absorbent article and recycled superabsorbent polymer derived from used absorbent article

    WO2020241025A1

  • Method for producing recycled superabsorbent polymer, method for producing superabsorbent polymer using recycled superabsorbent polymer, and recycled superabsorbent polymer

    WO2021044690A1